Вікові особливості професійного вигорання вчителів в умовах воєнного стану - MARININA, Vitaliia; TULIUPA, Vitaliia (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2025)
Background. The relevance of studying professional burnout remains constant, as it depends on the tasks and conditions of professional activity, which change both with the development of the relevant field and society as a whole. The armed aggression of the Russian Federation against Ukraine determines the specificity of these conditions through increased responsibility for the safety of students, chronic stress, increased anxiety, and violation of the basic need for security and stability in the world. Under such conditions, age as a factor of professional burnout influences the peculiarities of actualizing life and professional experience, as well as adaptive capabilities. The purpose of this study is to determine the peculiarities of age-related determination of teachers’ professional burnout during martial law. Methods. To carry out the aim and objectives of the study, the following methods were used: methodology for diagnosing professional burnout (K. Maslach, S. Jackson, adapted by N. Vodopianova), methodology ‘Coping behavior in stressful situations’ (S. Norman, D. Endler, D. James, M. Parker; adapted version by T. Kryukova); correlation analysis with a scatter plot to establish a connection between the motivation of professional and pedagogical activity, methodology for assessing the motivation of professional and pedagogical activity (K. Zamfir, modified version of A. Rean) and correlation analysis from the scatter plot to establish the relationship between the components of professional burnout and age, experience, behavioral, and motivational characteristics. The sample consisted of 50 teachers aged 30 to 64. Results. At the stage of professional development in teachers aged 30 to 44, pronounced emotional exhaustion is accompanied by a reduction in intrinsic motivation for professional activity and an increase in external negative motivation, as well as the active use of an emotionally oriented coping strategy, which exacerbates the existing psychoemotional stress. The presence of reduced intrinsic motivation contributes to greater depersonalization. Seeking social support can prevent a decline in personal achievements among teachers in this age group. At the stage of professional realization in teachers aged 45 to 64 years, the use of a problem-oriented coping strategy helps prevent emotional exhaustion. The dominance of intrinsic motivation precludes the development of depersonalization. Extrinsic motivation, both negative and positive, mitigates the impact of reduced personal achievements, serving as a confirmation of the social significance of work, professional status, and a means of maintaining personal authority. Сonclusions. It has been found that the age-related peculiarities of teachers’ professional burnout correspond in content to the stages of development of the subject of professional activity. Age is a cross-cutting determinant of professional burnout, as it mediates the relationship between the components of professional burnout and motivation, as well as coping strategies, thereby determining its specificity for different stages of professional development. The stage of professional activity is significant in terms of emotional exhaustion and depersonalization only for teachers aged 45 to 64 years, which makes it necessary to study personal characteristics and compare them with those of the age group from 30 to 44 years.